LGR4 is essential for maintaining β-cell homeostasis through suppression of RANK - Joanna Filipowska; Zelda Cisneros; Sneha S. Varghese; Nancy Leon-Rivera; Peng Wang; Randy Kang; Geming Lu; Yate-Ching Yuan; Hung-Ping Shih; Supriyo Bhattacharya; Sangeeta Dhawan; Adolfo Garcia-Ocaña; et al. (Molecular Metabolism)
Objective: Loss of functional β-cell mass is a major cause of diabetes. Thus, identifying regulators of β-cell health is crucial for treating this disease. The Leucine-rich repeat-containing G-protein-coupled receptor (GPCR) 4 (LGR4) is expressed in β-cells and is the fourth most abundant GPCR in human islets. Although LGR4 has regenerative, anti-inflammatory, and anti-apoptotic effects in other tissues, its functional significance in β-cells remains unknown. We have previously identified Receptor Activator of Nuclear Factor Kappa B (NFκB) (RANK) as a negative regulator of β-cell health. In this study, we assessed the regulation of Lgr4 in islets, and the role of LGR4 and LGR4/RANK stoichiometry in β-cell health under basal and stress-induced conditions, in vitro and in vivo. Methods: We evaluated Lgr4 expression in mouse and human islets in response to acute (proinflammatory cytokines), or chronic (high fat fed mice, db/db mice, and aging) stress. To determine the role of LGR4 we employed in vitro Lgr4 loss and gain of function in primary rodent and human β-cells and examined its mechanism of action in the rodent INS1 cell line. Using Lgr4fl/fl and Lgr4fl/fl/Rankfl/fl × Ins1-Cre mice we generated β-cell-specific conditional knockout (cko) mice to test the role of LGR4 and its interaction with RANK in vivo under basal and stress-induced conditions. Results: Lgr4 expression in rodent and human islets was reduced by multiple stressors. In vitro, Lgr4 knockdown decreased proliferation and survival in rodent β-cells, while overexpression protected against cytokine-induced cell death in rodent and human β-cells. Mechanistically, LGR4 protects β-cells by suppressing RANK- Tumor necrosis factor receptor associated factor 6 (TRAF6) interaction and subsequent activation of NFκB. Lgr4cko mice exhibit normal glucose homeostasis but increased β-cell death in both sexes and decreased β-cell proliferation and maturation only in females. Male Lgr4cko mice under stress displayed reduced β-cell proliferation and a further increase in β-cell death. The impaired β-cell phenotype in Lgr4cko mice was rescued in Lgr4/Rank double ko (dko) mice. Upon aging, both male and female Lgr4cko mice displayed impaired β-cell homeostasis, however, only female mice became glucose intolerant with decreased plasma insulin. Conclusions: These data demonstrate a novel role for LGR4 as a positive regulator of β-cell health under basal and stress-induced conditions, through suppressing the negative effects of RANK.